2016
DOI: 10.1016/j.phrs.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of V1A receptors in PVN modulates autonomic cardiovascular control

Abstract: The hypothalamic paraventricular nucleus (PVN) is a key integrative site for the neuroendocrine control of the circulation and of the stress response. It is also a major source of the neuropeptide hormone vasopressin (VP), and co-expresses V1a receptors (V1aR). We thus sought to investigate the role of V1aR in PVN in cardiovascular control in response to stress.Experiments were performed in male Wistar rats equipped with radiotelemetric device. The right PVN was transfected with adenoviral vectors (Ads) engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
(66 reference statements)
0
9
0
2
Order By: Relevance
“…AVP integrates neurosecretory and pre-autonomic populations of PVN neurons, through a mechanism deemed “volume transmission,” in which the release of a neuromodulator by dendrites into the extracellular medium influences the activity of juxtaposed neurons that are not anatomically connected by axon-dendrite synapses (Stern, 2015). The dendro-dendritic AVP release by the PVN has been shown to be important for autonomic control (Lozić et al, 2016) and neurosecretory and pre-autonomic PVN neurons have been shown to interact in this manner (Son et al, 2013). Ghrelin influences adiposity and energy utilization (Theander-Carrillo et al, 2006), volume transmission could potentially mediate these effects, since they depend on long-term alteration in neurotransmission/neuromodulation.…”
Section: Discussionmentioning
confidence: 99%
“…AVP integrates neurosecretory and pre-autonomic populations of PVN neurons, through a mechanism deemed “volume transmission,” in which the release of a neuromodulator by dendrites into the extracellular medium influences the activity of juxtaposed neurons that are not anatomically connected by axon-dendrite synapses (Stern, 2015). The dendro-dendritic AVP release by the PVN has been shown to be important for autonomic control (Lozić et al, 2016) and neurosecretory and pre-autonomic PVN neurons have been shown to interact in this manner (Son et al, 2013). Ghrelin influences adiposity and energy utilization (Theander-Carrillo et al, 2006), volume transmission could potentially mediate these effects, since they depend on long-term alteration in neurotransmission/neuromodulation.…”
Section: Discussionmentioning
confidence: 99%
“… 58 Their role is to prime magnocellular neurons and also to integrate the activity of neurons located in the magnocellular and the parvocellular parts of the PVN, 59 involved respectively in humoral and autonomic neural control of the circulation. 60 Lozić and colleagues 61 , 62 have demonstrated that upregulation of vasopressin V 1A and OT receptors in PVN modulates autonomic control of the cardiovascular system and changes the vulnerability of the rat phenotype to stress, thus pointing to possible targets for new drug development in cardioprotection from neurocardiogenic injuries.…”
Section: Causes Of Sudmentioning
confidence: 99%
“…Stress normally reduces BRS to permit concomitant BP and HR increase, preparing the animal for escape [185]. By transgenic generation of distinct rat phenotypes [186,187], those over-expressing OTR or V1aR in the PVN and by microinjecting selective blockers into the PVN, we found that the OTR rat phenotype has a blunted neurocardiogenic response to air-jet stress. OTR rats showed no baro-receptor desensitization and the increase of sympathetically-mediated BP variability was buffered compared to wild type controls.…”
Section: Somato-dendritic Release Of Vp and Ot And Cardiovascular Reactmentioning
confidence: 95%
“…In OTR rats the HR variability profile uncovered concomitant sympathetic (harmful) and vagal (protective) activation, while wild type rats exhibited solely sympathetic cardiac activation [188]. In rats over-expressing V1aR [186,187] in the PVN air-jet stress produced even greater baro-reflex desensitization than in wild type controls. In V1aR rats, the increase of sympathetically mediated BP variability and HR variability was greater than in wild type controls.…”
Section: Somato-dendritic Release Of Vp and Ot And Cardiovascular Reactmentioning
confidence: 99%